Brooklyn The Once and Future City - Campanella, Thomas J. 1964- (Princeton University Press, 2019)
A major new history of Brooklyn, told through its landscapes, buildings, and the people who made them, from the early seventeenth century to todayBrooklyn is a global brand both celebrated and scorned as the hippest place in America. Yet few know the back story of this extraordinary place. In Brooklyn: The Once and Future City, Thomas Campanella unearths long-lost threads of the urban past and weaves them into a narrative about the rise, fall, and reinvention of this most American city.From Vinegar Hill to Sheepshead Bay, and Bay Ridge to Brownsville, Campanella recounts the making of places familiar and long forgotten, bringing to life the individuals whose dreams, visions, rackets, and schemes forged the city we know today. He takes us through Brooklyn’s early days as homeland of the Leni Lenape and its transformation by Dutch colonists into a dense slaveholding region. We learn about English émigré Deborah Moody, whose town of Gravesend was the first founded by a woman in America. We see how wanderlust Yale dropout Frederick Law Olmsted used Prospect Park to anchor an open space system that was to reach back to Manhattan. And we witness Brooklyn’s emergence as a playland of racetracks and amusement parks celebrated around the world.From the teddy bear to transcontinental flight, Brooklyn has launched countless dreams. It was also a place of outsized failure, from Sam Friede’s bid to erect the world’s tallest building, to the long struggle to make Jamaica Bay the world’s largest deep-water seaport, and the star-crossed urban renewal, public housing, and highway projects that battered the borough. Campanella reveals how this immigrant Promised Land drew millions, fell tragic victim to its own social anxieties, and yet proved resilient enough to reawaken as a multicultural powerhouse and symbol for all things woke, fresh, and vital